1973
DOI: 10.1177/000348947308200624
|View full text |Cite
|
Sign up to set email alerts
|

Acute Histopathologic Inner Ear Changes in Deafness Due to Neomycin: A Case Report

Abstract: A case presentation of a patient receiving 8 of neomycin intramuscularly in preparation for surgery is presented. Acute renal failure and total deafness followed this injection and the temporal bones were removed on the seventeenth day postinjection. Histological findings showed inner and outer hair cell degeneration and a normal spiral ganglion count. There were some changes in the stria vascularis which were noted in the basal turn.The ototoxicity of neomycin is well known, but new case reports continue with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1976
1976
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“… 30 In other reports of ototoxicity from streptomycin 15 and gentamicin, 10,12,29 ganglion cell reduction was present throughout the cochlea. Additional studies have reported normal ganglion cell populations in ototoxicity associated with neomycin, 10,21,22 streptomycin, 18 kanamycin, 15,18 and gentamicin. 9,10,32 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 30 In other reports of ototoxicity from streptomycin 15 and gentamicin, 10,12,29 ganglion cell reduction was present throughout the cochlea. Additional studies have reported normal ganglion cell populations in ototoxicity associated with neomycin, 10,21,22 streptomycin, 18 kanamycin, 15,18 and gentamicin. 9,10,32 …”
Section: Discussionmentioning
confidence: 99%
“… 9,10,15,18,26,28 Only a few studies have included actual counts of the number of surviving ganglion cells and compared them with normal populations of ganglion cells in patients without ototoxicity. 12,19,20,22,27 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations